2013
DOI: 10.1111/jsr.12012
|View full text |Cite
|
Sign up to set email alerts
|

High‐altitude hypoxia and periodic breathing during sleep: gender‐related differences

Abstract: SUMMARYHigh-altitude exposure is characterized by the appearance of periodic breathing during sleep. Only limited evidence is available, however, on the presence of gender-related differences in this breathing pattern. In 37 healthy subjects, 23 male and 14 female, we performed nocturnal cardiorespiratory monitoring in the following conditions: (1) sea level; (2) first/ second night at an altitude of 3400 m; (3) first/second night at an altitude of 5400 m and after a 10 day sojourn at 5400 m. At sea level, a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 34 publications
6
43
0
2
Order By: Relevance
“…27 As a consequence of our findings, we believe that a study including specifically a sample of patients with CHF and sleep -disordered breathing would be justified. Considering that an optimization of heart failure treatment may alleviate central sleep apnea, 28,29 and in the wake of recent controversies regarding whether or not central sleep apnea should be specifically targeted in heart failure patients, a new therapeutic option targeting the pathophysiological basis of central apneas might be of particular interest.…”
Section: Figurementioning
confidence: 99%
“…27 As a consequence of our findings, we believe that a study including specifically a sample of patients with CHF and sleep -disordered breathing would be justified. Considering that an optimization of heart failure treatment may alleviate central sleep apnea, 28,29 and in the wake of recent controversies regarding whether or not central sleep apnea should be specifically targeted in heart failure patients, a new therapeutic option targeting the pathophysiological basis of central apneas might be of particular interest.…”
Section: Figurementioning
confidence: 99%
“…We would also postulate that the pauses observed in our study were likely physiological and also related to the effects of increased nocturnal vagal tone and sleep-disordered breathing which are well recognised at HA. 3,4 We believe the episode of SVT relates to the combination of sympathetic activation, hypoxia and sudden explosive exercise at HA. In addition to the factors outlined above the proarrhythmic effects of HA may be partly explained by other factors including acclimatization, changes in heart rate variability, sleep deprivation, dehydration and anxiety.…”
mentioning
confidence: 99%
“…However, these differences were not statistically significant. A recent study reported decreased periodic breathing in women, but found no difference in sleep quality between men and women (Lombardi et al, 2013). The acetazolamide group's younger age and lower Lake Louise Acute Mountain Sickness scores are characteristics typically associated with higher sleep quality.…”
Section: Discussionmentioning
confidence: 90%